Analysis of Transfer Pricing Method Determination in Transfer Pricing Documentation Practice at PT ABC Denpasar - N K Suandari; N S Hardika; I M Wijana (Journal of Applied Sciences in Accounting, Finance, and Tax, 2019)
PT ABC conducts an affiliated transaction with PT KLM and fulfills one of the conditions which require holding and storing transfer pricing documents in accordance with PMK No. 213 / PKM.03 / 2016. In carrying out its obligations, the first thing that PT ABC must do is to determine the transfer price method and PT ABC have to know the documents that need to be prepared in fulfilling its tax obligations. This study is intended to analyze the determination of transfer pricing method in the practice of transfer pricing at PT ABC and to find out the documents that should be prepared by PT ABC in the practice. The data used in this study are primary data obtained from interviews and secondary data obtained through documentation. The analysis technique used in this study is qualitative descriptive. Based on the results of the study, the transfer pricing method that suits with the condition of PT ABC is Comparable Uncontrolled Price/CUP. Documents that should be prepared by PT ABC are local documents.